2005
DOI: 10.1203/01.pdr.0000169968.07488.ad
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Glottal Resistance during Exposure to Severe Hypoxia in Neonatal Rats In Situ

Abstract: The neural control of respiratory airflow via the vocal fold is characterized by inspiratory abduction and postinspiratory (early expiratory) adduction causing decreases and increases in glottal resistance, respectively. The postinspiratory increase in glottal resistance plays a major role in braking the speed of expiratory airflow, to act against the high recoil pressure of the neonatal rat lung. In the present study, we investigated changes in upper airway patency during severe hypoxia in neonatal rats. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Evidence for the latter mechanism has been reported previously (Busselberg et al ., 2001; Markstahler et al ., 2002; Dutschmann & Paton, 2002). It has also been shown that post‐inspiratory activity is lost during hypoxic‐induced gasping (Dutschmann & Paton, 2005) and that post‐inspiratory neurons shift their phase of activation to coincidence with inspiration (Paton et al ., 2006). These previous results, in conjunction with the present data, support the notion that a shift from eupnea to gasping results in a reconfiguration of the respiratory network (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the latter mechanism has been reported previously (Busselberg et al ., 2001; Markstahler et al ., 2002; Dutschmann & Paton, 2002). It has also been shown that post‐inspiratory activity is lost during hypoxic‐induced gasping (Dutschmann & Paton, 2005) and that post‐inspiratory neurons shift their phase of activation to coincidence with inspiration (Paton et al ., 2006). These previous results, in conjunction with the present data, support the notion that a shift from eupnea to gasping results in a reconfiguration of the respiratory network (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was reported to occur specifically after blockade of brainstem glycinergic neurotransmission (Dutschmann and Paton, 2002a,b) and during severe hypoxia (Dutschmann and Paton, 2005). However, the verification of potentially reduced glycinergic inhibition within the ponto-medullary brainstem of Tau-P301L mice requires future experimental analysis.…”
Section: Enhanced Upper Airway Dysfunction During Hypercapniamentioning
confidence: 95%
“…Similar to opioids, inspiratory activities in newborns are depressed by severe hypoxia leading to tissue anoxia [1,3,4,15,17]. The latter studies and related work cited in these reports showed that breathing in a variety of newborn animal species continues at greatly reduced rate for anoxia periods >30 min, in particular in rodents, whereas they stop in adults after few minutes of oxygen depletion.…”
Section: Introductionmentioning
confidence: 91%